PENGEMBANGAN LMS BERBASIS GOOGLE SITES UNTUK MENGEMBANGKAN HOTS SISWA PADA MATA PELAJARAN GEOGRAFI - Devin Ardhi Saputra; Nofrion Nofrion (STKIP Singkawang, 2022)
This research aims to analyze the development of LMS based on Google Sites in Geography subject. The development of this LMS is intended to improve students' higher order thinking skills (HOTS) which can be used for online and offline learning. There are two research methods used i.e. ‘development research’ to develop a valid, practical, and effective Google Sites-based LMS and ‘experimental research’ to prove the effectiveness of Google Sites-based LMS in improving students' HOTS. The development model used is the Plomp which consists of three phases i.e. the Initial investigation phase, the Prototype development phase, and the assessment phase. Then a validity test is carried out involving three lecturers as validators, i.e. validation of media expert, material expert, and language and design expert with